The Porricondylini (Diptera: Cecidomyiidae: Porricondylinae) of Sweden revisited: descriptions of nineteen new species of ten genera, including a new genus - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2020)
The taxonomy of the tribe Porricondylini is revisited using male adult specimens from Sweden, whose morphology was studied by transmitted-light microscope. Results communicated here include both descriptions of new taxa (one genus, 19 species) and considerably expanded species distributions (five new Fennoscandian records). New taxa, all to be attributed to both authors, are Cassidoides cornutus sp. nov., Coccopsilis pectinata sp. nov., Cocc. recondita sp. nov., Cocc. scalpta sp. nov., Dendrepidosis lapponica sp. nov., D. upplandica sp. nov., Monepidosis difficilis sp. nov., M. hybrida sp. nov., Neocolpodia ombergensis sp. nov., Oelandyla rostrata gen. et sp. nov., Parepidosis kaltisbackensis sp. nov., Paurodyla serrata sp. nov., Porricondyla bidentula sp. nov., Porr. diversicornis sp. nov., Porr. gemina sp. nov., Porr. ottenbyensis sp. nov., Porr. pallidigenae sp. nov., Spungisomyia carinaolssonae sp. nov., and S. svemapro sp. nov. Species recorded in Fennoscandia for the first time are Bryocrypta angustata Mamaev (previously known from Latvia and European Russia), B. lobata Mamaev (previously Ukraine), Isocolpodia unidentata (Marikovskij) comb. nov. (previously Kazakhstan), Monepidosis duplicis Mamaev (previously Latvia and Far East Russia), and Zaitzeviola dubitabila (Mamaev & Zaitzev) (previously Far East Russia). The morphology of males of the newly recorded species is redescribed. Monepidosis tinnerti Jaschhof & Jaschhof, 2015 syn. nov. is revealed to be a junior synonym of M. duplicis Mamaev, 1998.